2014
DOI: 10.1111/maq.12071
|View full text |Cite
|
Sign up to set email alerts
|

Navigating and Circumventing a Fragmented Health System: The Patient's Pathway in the Sierra Madre Region of Chiapas, Mexico

Abstract: Mexico has implemented several important reforms in how health care for its poorest is financed and delivered. Seguro Popular, in particular, a recently implemented social insurance program, aims to provide new funds for a previously underfunded state-based safety net system. Through in-depth ethnographic structured interviews with impoverished farmers in the state of Chiapas, this article presents an analysis of Seguro Popular from the perspective of a highly underserved beneficiary group. Specific points of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…For example, using an experimental design, Spenkuch (2012) found that people enrolled in SP were less likely to use preventive care. In addition, Molina and Palazuelos (2014), using qualitative interviews, found that people with lower resources were less likely to use SP clinics because they were unable to request medications and the supply chain was weak; hospital inventories were empty and medication never arrived for some patients in this study. Moreover, as it is well known in the econometrics literature, propensity score methods do not fully account for unobservable (unmeasured) confounders.…”
Section: The Impact Of Social Health Insurance On Diabetesmentioning
confidence: 72%
“…For example, using an experimental design, Spenkuch (2012) found that people enrolled in SP were less likely to use preventive care. In addition, Molina and Palazuelos (2014), using qualitative interviews, found that people with lower resources were less likely to use SP clinics because they were unable to request medications and the supply chain was weak; hospital inventories were empty and medication never arrived for some patients in this study. Moreover, as it is well known in the econometrics literature, propensity score methods do not fully account for unobservable (unmeasured) confounders.…”
Section: The Impact Of Social Health Insurance On Diabetesmentioning
confidence: 72%
“…This represents a large work force addressing rural health needs, but there is a growing concern that, similar to interns beginning residency, Mexican pasantes would provide higher quality and safer care if they were supervised, supported, and continued to receive education during the social service year (4, 5). Innovative approaches to supporting and training pasantes during their social service year are sorely needed to help turn Mexico's universal enrollment into true universal effective coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 3–4 days are assigned as vacation. This model of concentrating days away from the community purposely differs from the traditional model of pasantes having 1–2 days off a week, because the long trips required to exit and then re-enter isolated rural communities tend to diminish actual time off and promote absenteeism (4, 5). CES-supported clinics also receive supplemental supplies to ensure there are no stock-outs of essential medicines, diagnostic tests, and basic infection control supplies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They spoke to me about the “ugly” experiences they had in other clinics and the vulnerability they felt when their children were placed in the care of rude and disrespectful doctors. Such experiences are not isolated to the field of cleft treatment; numerous studies have examined negative patient experiences in Mexican biomedical institutions (Finkler ), especially when they are from low socioeconomic or indigenous backgrounds (Molina and Palazuelos ; Smith‐Oka ).…”
Section: Cleft Care In Mexico: the View From Above And Belowmentioning
confidence: 99%